Financial Behavior in Banking: A Systematic Review with Structured Thematic Synthesis of Risk-Taking and Bank Performance - Nuryamin Budi; Wa Ode Nella Arnianti; Ninar Pratiwi; Sri Asyuningsih; Ardian Dasaly; Ovaldin (Indonesian Journal of Taxation and Accounting, 2026)
Purpose - This study reviews the relationship between institutional financial behavior and bank performance. Financial behavior is reflected in risk-taking, capital behavior, income diversification, governance-related behavior, and liquidity management. Methods - The study applies a systematic literature review based on PRISMA 2020. From 368 Scopus records, 80 full-text articles were screened. After eligibility assessment, 17 empirical studies were retained for thematic synthesis, with 8 studies highlighted for detailed comparison. Findings - The review finds that institutional financial behavior significantly affects bank performance, but the effects are heterogeneous. Capital behavior tends to improve stability, although it may reduce profitability. Governance-related behavior supports efficiency and risk control. Income diversification generally strengthens profitability and stability, especially during crisis periods. Liquidity behavior may improve returns but can also increase risk exposure. Research Implications - The findings suggest the need for more consistent measurement and stronger integrated frameworks in banking research. They also help managers and regulators balance profitability, stability, governance, and risk management. Originality - This study positions institutional financial behavior as an overarching construct linking capital decisions, risk-taking, governance oversight, liquidity management, prudential reporting, and bank performance assessment.